Whistleblowing, Love Of Money, Machiavellian In Accounting Mentallity Perspective Towards Fraud Tendencies - Wikrama Tungga Dewi, V Ananta; Prasetyo, Henri; Perdhiansyah; Rahmaniar, Risti (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to determine the effect of whistleblowing, love of money, machiavellian for mental accounting perspective on the tendency accounting fraud. This type of research is quantitative. The data collection method used in this study refers to primary data sources in the form of questionnaires. The results showed that whistleblowing has significant effect on the tendency of fraud accounting at 0,001 < 0,05. The love of money and Machiavellian have no significant effect on the tendency of fraud accounting. The love of money has 0,537 > 0,5. The Machiavellian has 0,541 > 0,05.